Same game, different worlds? General conditions, perceived stress, and associations between stress and past season injuries in elite female and male ice hockey players - Wörner, T.; Kauppinen, S.; Eek, F. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Ice hockey is played by women and men but the arena they play in may differ substantially. Potential differences in general conditions to play the sport may be associated to perceived stress, which has shown to be related to athletic injury in other sports. Therefore, this study aimed to describe and compare general conditions for playing ice hockey, stress levels, and the association between perceived stress and injury occurrence among elite female and male players.